Enhancement of ethylbenzene removal from contaminated gas and corresponding mechanisms in biotrickling filters by a biosurfactant from piggery wastewater. (1st January 2021) - Guo, Junyuan; Gao, Qifan
Abstract: This study prepared a biosurfactant by using piggery wastewater to enhance ethylbenzene removal from contaminated gas in a biotrickling filter (BTF). Experiments were conducted to investigate the enhancement of ethylbenzene removal and the biofilm characteristics in present of the biosurfactant. Results demonstrated that the optimal biosurfactant concentration was 0.1 CMC and the corresponding ethylbenzene removal rate was 87.2%, much higher than that (68.9%) achieved in free of biosurfactant. The inlet ethylbenzene concentration and the empty bed residence time (EBRT) affected ethylbenzene removal as well. In present of 0.1 CMC of biosurfactant, ethylbenzene removal rate decreased from 87.2% to 72.2% with the increasing inlet ethylbenzene from 1000 to 2200 mg/m 3, and decreased from 91.1% to 42.7% with the EBRT shorten from 30 to 7.5 s. For the enhancement mechanisms of ethylbenzene removal in BTF, the biosurfactant changed the contents of extracellular polymers (EPS) and decreased negative surface charge of the biofilm in the BTF, which improved the mass transfer of ethylbenzene to biofilm and facilitated the aggregation of microbes, and further improved the removal of ethylbenzene. All in all, the biosurfactant would be a feasible way to enhance the removal of ethylbenzene by the BTF. Graphical abstract: Image 1 Highlights: A biosurfactant was successfully harvested from piggery wastewater. The biosurfactant could be biodegraded by and was not toxic to microbes. The biosurfactant was proved to be able to enhance ethylbenzene removal in BTF. Surface characteristic of the biofilm in BTF was discussed. Mechanism in the presence of the biosurfactant in ethylbenzene removal was evaluated.